Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Best Practice Data Standards for Discrete Chemical Oceanographic Observations - Li-Qing Jiang; Denis Pierrot; Rik Wanninkhof; Richard A. Feely; Bronte Tilbrook; Simone Alin; Leticia Barbero; Robert H. Byrne; Brendan R. Carter; Andrew G. Dickson; Jean-Pierre Gattuso; Dana Greeley; et al. (Frontiers in Marine Science, 2022)
Effective data management plays a key role in oceanographic research as cruise-based data, collected from different laboratories and expeditions, are commonly compiled to investigate regional to global oceanographic processes. Here we describe new and updated best practice data standards for discrete chemical oceanographic observations, specifically those dealing with column header abbreviations, quality control flags, missing value indicators, and standardized calculation of certain properties. These data standards have been developed with the goals of improving the current practices of the scientific community and promoting their international usage. These guidelines are intended to standardize data files for data sharing and submission into permanent archives. They will facilitate future quality control and synthesis efforts and lead to better data interpretation. In turn, this will promote research in ocean biogeochemistry, such as studies of carbon cycling and ocean acidification, on regional to global scales. These best practice standards are not mandatory. Agencies, institutes, universities, or research vessels can continue using different data standards if it is important for them to maintain historical consistency. However, it is hoped that they will be adopted as widely as possible to facilitate consistency and to achieve the goals stated above.

Opposing Indirect Effects of Domestic Herbivores on Saltmarsh Erosion - Jordi F. Pagès; Stuart R. Jenkins; Tjeerd J. Bouma; Elwyn Sharps; Martin W. Skov (Ecosystems, 2019)

Assessing uncertainties in crop and pasture ensemble model simulations of productivity and N 2 O emissions - Fiona Ehrhardt; Jean‐François Soussana; Gianni Bellocchi; Peter Grace; Russel McAuliffe; Sylvie Recous; Renáta Sándor; Pete Smith; Val Snow; Massimiliano de Antoni Migliorati; Bruno Basso; Arti Bhatia; et al. (Global Change Biology, 2018)
Simulation models are extensively used to predict agricultural productivity and greenhouse gas emissions. However, the uncertainties of (reduced) model ensemble simulations have not been assessed systematically for variables affecting food security and climate change mitigation, within multi‐species agricultural contexts. We report an international model comparison and benchmarking exercise, showing the potential of multi‐model ensembles to predict productivity and nitrous oxide (N 2 O) emissions for wheat, maize, rice and temperate grasslands. Using a multi‐stage modelling protocol, from blind simulations (stage 1) to partial (stages 2–4) and full calibration (stage 5), 24 process‐based biogeochemical models were assessed individually or as an ensemble against long‐term experimental data from four temperate grassland and five arable crop rotation sites spanning four continents. Comparisons were performed by reference to the experimental uncertainties of observed yields and N 2 O emissions. Results showed that across sites and crop/grassland types, 23%–40% of the uncalibrated individual models were within two standard deviations ( SD ) of observed yields, while 42 (rice) to 96% (grasslands) of the models were within 1 SD of observed N 2 O emissions. At stage 1, ensembles formed by the three lowest prediction model errors predicted both yields and N 2 O emissions within experimental uncertainties for 44% and 33% of the crop and grassland growth cycles, respectively. Partial model calibration (stages 2–4) markedly reduced prediction errors of the full model ensemble E‐median for crop grain yields (from 36% at stage 1 down to 4% on average) and grassland productivity (from 44% to 27%) and to a lesser and more variable extent for N 2 O emissions. Yield‐scaled N 2 O emissions (N 2 O emissions divided by crop yields) were ranked accurately by three‐model ensembles across crop species and field sites. The potential of using process‐based model ensembles to predict jointly productivity and N 2 O emissions at field scale is discussed.

Understanding Climate Adaptation on Public Lands in the Upper Midwest: Implications for Monitoring and Tracking Progress - Christine M. Anhalt-Depies; Tricia Gorby Knoot; Adena R. Rissman; Anthony K. Sharp; Karl J. Martin (Environmental Management, 2016)

Fairway patch - a serious emerging disease of couch (syn. bermudagrass) [Cynodon dactylon] and kikuyu (Pennisetum clandestinum) turf in Australia caused by Phialocephala bamuru P.T.W. Wong & C. Dong sp. nov. - P. T. W. Wong; C. Dong; P. M. Martin; P. J. Sharp (Australasian Plant Pathology, 2015)

Methanogenic potential of Arctic and Antarctic subglacial environments with contrasting organic carbon sources - Marek Stibal; Jemma L. Wadham; Grzegorz P. Lis; Jon Telling; Richard D. Pancost; Ashley Dubnick; Martin J. Sharp; Emily C. Lawson; Catriona E. H. Butler; Fariha Hasan; Martyn Tranter; Alexandre M. Anesio (Global Change Biology, 2012)
Subglacial environments are largely anoxic, contain organic carbon ( OC ) overridden by glacier ice during periods of advance, and harbour active microbial communities. This creates favourable conditions for OC degradation via methanogenesis. It has been hypothesized that OC beneath ice sheets is converted to methane ( CH 4 ) and may be released to the atmosphere during retreat. However, there are limited data available to support this contention. Here, we present new data on the abundance, diversity and activity of methanogenic archaea and the amount and character of OC in subglacial sediments from Arctic and Antarctic glacial systems based on different substrate types. We employed long‐term laboratory incubations to quantify the CH 4 production potential in different subglacial settings. Significant numbers of methanogens (up to 7 × 10 4 cells g −1 ) were detected in the samples and clones of Methanomicrobiales and Methanosarcinales were identified in clone libraries. Long lag periods (up to >200 days) were observed before significant CH 4 concentrations were measured. We report order of magnitude differences in rates of CH 4 production (10 1 –10 5 fmol g −1 d −1 ) in different subglacial sediments, reflecting contrasts in the origin of the sediment and the OC character. Hence, we predict that contrasting rates of CH 4 production are likely to occur beneath glaciers and ice sheets that overran different types of substrate. We subsequently estimated the potential for CH 4 production beneath the Laurentide/Inuitian/Cordilleran and Fennoscandian Ice Sheets during a typical 85 ka Quaternary glacial/interglacial cycle. CH 4 production from lacustrine‐derived OC is likely to be an order of magnitude higher (~6.3–27 Pg C) than that from overridden soils (~0.55–0.68 Pg C), possibly due to a difference in lability between lacustrine and soil OC . While representing a fraction of the entire OC pool (~418–610 Pg C), this finding highlights the importance of considering the character of different OC pools when calculating subglacial CH 4 production.

Prokaryotic diversity in sediments beneath two polar glaciers with contrasting organic carbon substrates - Marek Stibal; Fariha Hasan; Jemma L. Wadham; Martin J. Sharp; Alexandre M. Anesio (Extremophiles, 2012)

Near‐surface‐temperature lapse rates on the Prince of Wales Icefield, Ellesmere Island, Canada: implications for regional downscaling of temperature - Shawn J. Marshall; Martin J. Sharp; David O. Burgess; Faron S. Anslow (International Journal of Climatology, 2007)
Screen temperatures were monitored from May 2001 to April 2003 in an array of 25 sites on the Prince of Wales Icefield, Ellesmere Island, Canada. The observational network covered an area of ca 15 650 km 2 and spanned an altitude ranging from 130 to 2010 m above sea level. The spatial array provides a record of near‐surface‐temperature lapse rates and mesoscale temperature variability on the icefield. The mean daily lapse rate in the 2‐year record is − 4.1° C km −1 , with an average summer lapse rate of − 4.3° C km −1 . Surface‐temperature lapse rates in the region are therefore systematically less than the free‐air lapse rates that are typically adopted for extrapolations of sea‐level temperature to higher altitudes. Steep lapse rates, resembling moist adiabatic rates in the free air (−6 to − 7° C km −1 ), are more common in summer at our site and are associated with enhanced cyclonic activity (low‐pressure and high relative vorticity) and southerly flow aloft. In contrast, northerly, anticyclonic flow prevails when summer lapse rates are weak (above − 2° C km −1 ). The low surface‐temperature lapse rates and their systematic synoptic variability have important implications for applications that require downscaling or extrapolation of surface‐ or boundary‐layer temperatures, such as modelling of glacier mass balance. We illustrate this in an analysis of observed versus modelled snowmelt on the icefield. Copyright © 2006 Royal Meteorological Society.

Fluxes of semivolatile organochlorine compounds in Bow Lake, a high‐altitude, glacier‐fed, subalpine lake in the Canadian Rocky Mountains - Jules M. Blais; David W. Schindler; Martin Sharp; Eric Braekevelt; Melissa Lafreniěre; Karen McDonald; Derek C. G. Muir; William M. J. Strachan (Limnology and Oceanography, 2001)
The fluxes of several organochlorine compounds (OCs) to and from a high‐altitude lake were calculated to determine the relative contributions of rainfall, snowfall, runoff, gas absorption and volatilization, sedimentation, and outflow. Runoff inputs, particularly from a glaciated catchment, and gas absorption were major sources of many OCs. Losses by volatilization, outflow, and sedimentation were also important transport pathways for most OCs. We observed a net deposition of hexachlorocyclohexanes (HCHs) and DDT to Bow Lake by gas exchange, whereas hexachlorobenzene, chlordanes, and most polychlorinated biphenyls were seen to volatilize to the air. The insecticide lindane (γHCH), widely applied across Canada as a seed dressing in early spring, was absorbed by Bow Lake in early summer but gradually equilibrated with water as the summer progressed. This was the result of lower concentrations of γHCH in air and rising air temperatures in late summer. Results indicate that glacially derived tributary inputs are dominant sources of persistent organic pollutants to these glacier‐fed mountain lakes and that smaller contributions may derive from air‐water gas exchange. This study highlights the importance of glacial sources of OCs to mountain lakes and corroborates recent evidence of OC contamination in glacially derived aquatic systems.